PENGARUH PEMANFAATAN SITUS GOOGLE SEBAGAI SUMBER BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI DI SMA NEGERI 3 SURAKARTA - -, Ita Marshelita Arumdani -; -, Bambang Wasito Adi -; -, Muhammad Sabandi - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The purpose of this study is to determine: (1) The influence of the use of google site as a source of learning and achievement motivation on the achievement of learning on the subjects Economics class XI IPS SMA Negeri 3 Surakarta year 2016/2017. (2) The influence of learning motivation on learning achievement in Economics class XI IPS SMA Negeri 3 Surakarta Lesson Year 2016/2017. (3) The impact of the use of google site as a source of learning and learning motivation on learning achievement in the subjects of Economics class XI SMA Negeri 3 Surakarta Lesson Year 2016/2017.This research is quantitative descriptive research by doing a hypothesis test. This research is located at SMA Negeri 3 Surakarta. The population in this study were students of class XI IPS which amounted to 86 students. Samples were taken as many as 86 students with total sampling technique (Complete Enumeration). The data collection technique used is a questionnaire or questionnaire. Data analysis technique used is multiple regression.The results showed that: (1) There is a positive and significant influence between the use of google site as a source of learning on the achievement of learning in the economic subjects of class XI IPS in SMA Negeri 3 Surakarta obtained tcount value of confidence of 3.144, while the value of t table of 1.989, obtained result that 3,144> 1,989. (2) There is a positive and significant influence between learning motivation on learning achievement on economic subjects of class XI IPS in SMA Negeri 3 Surakarta obtained the value of t variable achievement motivation that is equal to 2,258 while t table value 1,988, obtained result that 2,258> 1,988. (3) There is a positive and significant influence between the use of google site as a source of learning and learning motivation together to the achievement of learning on the economic subjects of class XI IPS in SMA Negeri 3 Surakarta is shown with F value of 9,135, while the F table value of 3.191, because of 9,135> 3,191. The amount of influence of variable use of google site as a source of learning and motivation to learn achievement learners derived from R square calculation of 28.1%, while the rest (100% - 28.1% = 71.9%) is influenced by other causes such as school environment factors, family environment factors, interest in learning, learning media and so forth.